Tranexamic Acid for the Prevention of Blood Loss After Cesarean Delivery. Issue 9 (September 2021) - Sentilhes, Loic; Sénat, Marie V.; Le Lous, Maela; Winer, Norbert; Rozenberg, Patrick; Kayem, Gilles; Verspyck, Eric; Fuchs, Florent; Azria, Elie; Gallot, Denis; Korb, Diane; Desbrière, Raoul; et al.
Abstract : (Abstracted from N Engl J Med 2021;384:1623–1634) Uterotonic agents are recommended to prevent postpartum hemorrhage (PPH). Tranexamic acid (TXA) has emerged as another medical approach to prevent blood loss after delivery.